2018
DOI: 10.1159/000486816
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Tumor-Associated Macrophages in Colorectal Carcinoma Progression

Abstract: Tumor-associated macrophages (TAMs) are one of the most abundant immune cells in the tumor microenvironment, and they play a pivotal role in prompting the various tumor growth. However, the role of TAMs in colorectal carcinoma (CRC) is controversial, because a few papers report that TAMs is beneficial to CRC patients. In this review, we discuss the good or bad roles of TAMs in CRC progression. Interestingly, recent studies provide strong evidence that TAMs facilitate CRC growth, but do not exert tumor suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 55 publications
1
92
0
1
Order By: Relevance
“…The accentuation on the usage of M1/M2 ratio in prognosticating cancer is supported by the ambiguities concerning the sole densities of TAMs in patients' prognosis (29,30). For instance, although TAMs in general have negative effect on the gastric patients' prognosis in many studies (19,31,32), some studies showed opposing results (33)(34)(35).…”
Section: M1/m2 Ratio As the More Amenable Means Of Cancer Prognosticamentioning
confidence: 99%
“…The accentuation on the usage of M1/M2 ratio in prognosticating cancer is supported by the ambiguities concerning the sole densities of TAMs in patients' prognosis (29,30). For instance, although TAMs in general have negative effect on the gastric patients' prognosis in many studies (19,31,32), some studies showed opposing results (33)(34)(35).…”
Section: M1/m2 Ratio As the More Amenable Means Of Cancer Prognosticamentioning
confidence: 99%
“…Our study also included the assessment of macrophage density, at least two populations of macrophages with opposite immunological roles have been identified; as double edge swords, the M1 (classically activated) type with a proinflammatory antitumoral function and the M2 (alternatively activated) type with an immunosuppressive protumoral function [24,25]. It has been postulated that most of the tumor-associated macrophages belong to the M2 subtype [26].…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer, the role of macrophages is controversial, with some authors claiming that a high infiltration is associated with better prognosis, while others report that their presence is associated with increased tumor progression-associated activities [5]. Our group has previously evidenced that macrophages induce gastric and colon cancer cell invasion, in a process partially mediated by secreted factors, and that the secretome of macrophages differs from that of macrophages co-cultured with cancer cells [6].…”
Section: Introductionmentioning
confidence: 95%